Model Integrasi K3 dan Manajemen Risiko untuk Meningkatkan Daya Saing Organisasi - Husna, Afiyah Tasya; Suluhniate, Marsyaliya; Harahap, Mufidah; Hasibuan, Abdurrozzaq (Melati Institute, 2025)
In an era of increasingly complex global competition, organizations are required to implement innovative strategies to improve their competitiveness. One relevant approach is the integration of the Occupational Safety and Health (OHS) system with risk management. This study aims to examine the integration model of OHS and risk management and its impact on organizational competitiveness through a literature study of ten relevant scientific journals. The method used is a systematic literature review with a thematic synthesis approach to articles from the last five years. The results of the study indicate that the integration of OHS and risk management not only serves to reduce the incidence of work accidents, but also encourages operational efficiency, increased productivity, financial stability, and corporate reputation. Supporting factors for the success of this integration include top management commitment, utilization of information technology, strong organizational culture, and human resource development. Thus, this integration model is a long-term strategic investment that provides significant added value to the sustainability and competitiveness of organizations in various industrial sectors.